Perbandingan Penggunaan 3 Jenis Pipa untuk Sistem Penyediaan Air (Kajian Kasus Kawasan Industri Terpadu Kabupaten Batang) - Widiyatmoko, Widiyatmoko; Soenarto, Bambang; Kristina, Kristina (Universitas Batanghari Jambi, 2024)
Batang Regency is one of the areas located on the north west coast of Central Java province. Batang Regency is located in a strategic position, this area is traversed by primary arterial roads that connect West Java and DKI Jakarta with cities in Central Java and East Java Provinces. Batang Regency is divided into 15 sub-districts consisting of 239 villages, 9 sub-districts, 936 hamlets, 3,680 neighborhood units (RT) and 1,009 community units (RW). The total area of Batang Regency is 78,864.16 Ha. The widest sub-district is Subah District, which is 83.52 Ha (10.59%), while the smallest is Warungasem District, which is 23.55 Ha (2.99%) of the total area of Batang Regency. The Central Government's program to encourage the sector to strengthen the industrial sector in Indonesia, namely one of the developments in the Batang industry. The Government provides supporting facilities in the development of the Batang Industrial area through APBN financing. The Batang Industrial Estate has around 4,300 hectares of land to develop, for the first phase it will develop a land area of 450 hectares. To support the supply of drinking water in this area, PERUMDA of Sendang Kamulyan Drinking Water, Batang Regency will supply drinking water which will take water from the raw water source of the Bangkangan spring at 100 liters/second and will be supplied to the Industrial Area at 80 l/s. For the analysis of the drinking water supply system in this industrial area, the Epanet 2.2 program will be used by comparing the hydraulic analysis of the use of HDPE, PVC and iron pipe types/materials, residual pressure and diameter as well as calculating the amount of investment based on the type of pipe material. The results of running Epanet 2.2 on HDPE, Iron and PVC pipes with remaining water pressure at the end of the pipe at the KITB Junction, the remaining pressure is more than 10 meters, meaning that the water has flowed with sufficient criteria in the service area. Based on the analysis taking into account efficiency, the selected pipe is HDPE with an investment value of Rp. 20,273,230,410. The recommendations given for SPAM KITB, can use HDPE pipes, apart from lower costs HDPE pipes have a better roughness coefficient than PVC pipes and iron pipes and can also minimize pipe leaks. Lessons from this study with Epanet Software can calculate water hydraulics in the piping system such as water velocity, the furthest remaining water pressure can be known quickly, can determine the type and specifications of pipes used for the study area and known cost efficiency based on the type of iron, PVC and HDPE pipes.